Sciaenid fishery off Visakhapatnam with some aspects of population dynamics of Johnius carutta (Bloch) - Rajkumar, U; Rao, K Narayana; Kingsley, H Jose (Indian Journal of Fisheries, 2011)
The average annual catch of sciaenids by small-mechanized units operated off Visakhapatnam was 465 t, which formed 5.76% of the total landings. Of the thirteen species of sciaenids landed, Johnius carutta and Nibea maculata dominated the fishery. The estimated asymptotic length (Lâˆ) and growth constant (K-year) of J. carutta were 295 mm and 0.40, respectively. The size at first maturity was 154 mm and the spawning season was during March - May. The mortality rates Z, F and M were 3.02, 2.05 and 0.97 respectively. The exploitation rate of 0.68 indicated heavy exploitation of the species. The yield/ recruit curves showed that the exploitation rate could be brought down to E max (0.57) without affecting the catch.